Roaring Youth Subculture as Street Gang in A Clockwork Orange - F. Berna Uysal (Ideas: Journal of English Literary Studies)
Youth subcultures mostly arise within mainstream cultures that determine the norms of the way of living in communities. The antagonistic way of thinking and manners of youth subcultures emerge together with unique dialects, dressing styles and behavioural patterns. The youth subcultures aim to shatter the predetermined and inherited notions, that are patriarchal, restrictor and discriminator, in the public sphere therefore they are mostly found violent, rebellious and peevish. This study aims to show how youth subcultures emerge from mainstream cultures in societies as reactions to dominant notions of communities and the ways to control them through the excerpts from Anthony Burgess’s A Clockwork Orange (1962). The work will be examined briefly throughout this study to show that with argots and styles, the members of the subcultures, which may mostly be derived from violent actions, become dissidents in the controlling governments. The government’s aim is to penalise dissidents with forced punishments through its institutions, such as prisons or/and asylums. However, any forceful action that is against free will, even if it is innately good, is bad, and dissidents become the victims of the government because the governmental punishments do not pave the way to betterment, on the contrary, its forced solutions against anomalous agents—any agent that performs unorthodoxly—in the communities exacerbate the predicament further.